2019
DOI: 10.1007/jhep10(2019)281
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic creation of baby bubble universe with small positive cosmological constant

Abstract: We investigate the decay of metastable de Sitter, Minkowski and anti-de Sitter vacua catalyzed by a black hole and a cloud of strings. We apply the method to the creation of the four dimensional bubble universe in the five dimensional anti-de Sitter spacetime recently proposed by Banerjee, Danielsson, Dibitetto, Giri and Schillo [1]. We study the bounce action for the creation and find that the bubble with very small cosmological constant, of order Λ (4) /M 2 4 ∼ 10 −120 , is favored by the catalysis by assumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Such modes can appear, for example, when there is a black hole in the bulk spacetime. 9 In our case, with the source on the shell, we no longer have pure AdS spacetime. Let us use this fact to postulate that such non-propagating modes do exist in our case, and let us study the gravitational propagator between two bulk points across the shell for these modes.…”
Section: Linearized Gravity In Momentum Spacementioning
confidence: 90%
“…Such modes can appear, for example, when there is a black hole in the bulk spacetime. 9 In our case, with the source on the shell, we no longer have pure AdS spacetime. Let us use this fact to postulate that such non-propagating modes do exist in our case, and let us study the gravitational propagator between two bulk points across the shell for these modes.…”
Section: Linearized Gravity In Momentum Spacementioning
confidence: 90%
“…The role of the stretched strings, and the nature of four dimensional gravity, was subsequently elaborated in [2,3]. By computing the bounce action of the shell in the presence of a cloud of strings and a Schwarzschild mass in five dimensions, [8] showed that the preferred nucleation channel is a bubble with slightly sub-critical tension, giving a phenomenologically realistic four dimensional cosmological constant. Recently, a top down construction of a (p + 1) dimensional dS shellworld, via the nucleation of a p dimensional bubble in an AdS p+2 × S q bulk, was done for p = 1, 5 in ten dimensional non-supersymmetric string theory by [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its advantage is twofold: it evades the swampland constraints of constructing 'fundamental' dS vacua based on pure compactifications of string theory [11] and, at the same time, it provides a concrete realisation of a braneworld in string theory with an inside-outside construction (in contrast to the inside-inside structure of RS or KR models). In [12][13][14][15] the physics of nucelation in AdS 5 was further studied, while [16] discusses a concrete realization of the dark bubble throguh a resolved Calabi-Yau conifold.…”
Section: Introductionmentioning
confidence: 99%